2020
DOI: 10.1002/jccs.201900399
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory studies of effects of boron replacement on the structure and property of RDX and HMX

Abstract: In this study, based on two model nitramine compounds hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and octahydro-1,3,5,7-tetranitro-1,3,5, 7-tetrazocine (HMX), two series of new energetic molecules were designed by replacing carbon atoms in the ring with different amounts of boron atoms, their structures and performances were investigated theoretically by the density functional theory method. The results showed that the boron replacement could affect the molecular shape and electronic structure of RDX and HMX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The presence of PETN in the new designed molecules increased the heat of detonation tremendously as seen from Table 3. Similar to the studies in the literature [30,[36][37][38], it is seen that the explosion heat values increase by changing the substitution groups of energetic materials or adding new groups. This means that the new energetic materials obtained will generate more heat compared to the original explosives.…”
Section: Heat Of Detonationsupporting
confidence: 81%
See 1 more Smart Citation
“…The presence of PETN in the new designed molecules increased the heat of detonation tremendously as seen from Table 3. Similar to the studies in the literature [30,[36][37][38], it is seen that the explosion heat values increase by changing the substitution groups of energetic materials or adding new groups. This means that the new energetic materials obtained will generate more heat compared to the original explosives.…”
Section: Heat Of Detonationsupporting
confidence: 81%
“…Consequently, relations in the second column of Table1 have been employed in the calculations. Wu et al [30] developed two series of novel energetic molecules by substituting carbon atoms in the rings of RDX and HMX compounds with varying quantities of boron atoms, and their performance was studied theoretically using the density functional theory approach (DFT-B3LYP 6-31G (d, p) level). The findings revealed that features including electrical structure, formation heat, density, and sensitivity may all be altered.…”
Section: Explosive Propertiesmentioning
confidence: 99%